2020
DOI: 10.1108/bij-11-2019-0489
|View full text |Cite
|
Sign up to set email alerts
|

Green competencies: insights and recommendations from a systematic literature review

Abstract: PurposeThis study conceptualises the construct – green competencies. The concept is in the niche stage and needs further elaboration. Hence, to address the research gap, this study follows the steps proposed by Tranfield et al. (2003). The major part of the study comprises descriptive analysis and thematic analysis. Descriptive analysis of the selected 66 articles was examined with the classification framework, which contains year-wise distribution, journal-wise distribution, the focus of the concept, the econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 137 publications
3
37
0
Order By: Relevance
“…This result refers to an imperative finding of the study that green training is an inevitable business strategy to instil the required level of awareness, abilities, skills, knowledge, attitudes and behaviours among the employees. The results are consistent with the previous studies (Bozionelos et al, 2019;Cabral and Dhar, 2020;Joshi and Dhar, 2020) which emphasize the significance of green training in developing pro-environment competencies among employees. It can, finally, be inferred that green training facilitates the provision of green competencies to equip the employees for achieving an organization's environmental goals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result refers to an imperative finding of the study that green training is an inevitable business strategy to instil the required level of awareness, abilities, skills, knowledge, attitudes and behaviours among the employees. The results are consistent with the previous studies (Bozionelos et al, 2019;Cabral and Dhar, 2020;Joshi and Dhar, 2020) which emphasize the significance of green training in developing pro-environment competencies among employees. It can, finally, be inferred that green training facilitates the provision of green competencies to equip the employees for achieving an organization's environmental goals.…”
Section: Discussionsupporting
confidence: 92%
“…The term green competencies is known as an individual's capacity to interact with the natural environment in a constructive and efficient manner (Steele, 1980). According to Cabral and Dhar (2020), green competencies is a multidimensional construct which has six main dimensions including awareness, knowledge, skills, abilities, attitudes and behaviours. Green awareness enables the employees to get conscious about the adverse impact of their activities on natural environment (Gadenne et al, 2009).…”
Section: Green Competenciesmentioning
confidence: 99%
“…The finding of this hypothesis is also consistent with other studies that have also found this relationship under various conditions [56,71]. As a result, universities need to foster green competencies through adequate green training, which emphasizes employee sensitivity towards environmental protection and sustainable development, as well as plays a major role in building an organizational citizenship behavior towards the environment in the workplace [71]. Similarly, the results of the third hypothesis revealed the positive and significant influence of green competencies with green environmental performance which is also congruent to earlier studies [28].…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, the results for the second hypothesis showed the positive and significant impact of green training with green competencies. The finding of this hypothesis is also consistent with other studies that have also found this relationship under various conditions [56,71]. As a result, universities need to foster green competencies through adequate green training, which emphasizes employee sensitivity towards environmental protection and sustainable development, as well as plays a major role in building an organizational citizenship behavior towards the environment in the workplace [71].…”
Section: Discussionsupporting
confidence: 89%
“…It is important to appreciate that GHRM does not only focus on creating environmental awareness among employees but holistically considers the overall improvement in the socio-economic well-being of employees and the organization (Obaid and Alias, 2015). Thus, GHRM has mammoth potential to solve environmental challenges and help to execute green strategies (Cabral and Dhar, 2020). Firms that deploy GHRM policies can put their resources into effective and efficient use (Galleli et al, 2019) and achieve a competitive advantage (Paill e et al, 2020).…”
Section: Green Human Resource Management (Ghrm)mentioning
confidence: 99%